Process Parameters for Fermentation in a Rotary Disc Reactor for Optimum Microbial Cellulose Production using Response Surface Methodology - Khairul Azly Zahan; Norhayati Pa'e; Ida Idayu Muhamad (BioResources, 2014)
In this study, microbial cellulose production by Acetobacter xylinum 0416 using standardized liquid pineapple waste was carried out in a 4-L rotary disc reactor (RDR). The objective of this study was to optimize the process parameters for production of microbial cellulose in the RDR. The effects of the disc rotation speed (5 to 12 rpm), pH (3.5 to 7.5), fermentation period (3 to 6 days), and inoculum concentration (3 to 20% v/v) on the microbial cellulose production were investigated. The optimum microbial cellulose yield was obtained using 10% (v/v) of inoculum concentration, whereby four days’ duration gave the most productive yield. In addition, the highest production of microbial cellulose was obtained at a low disc rotation speed of 7 rpm and a pH of 5.0. Analysis of data performed a high coefficient of determination value (R2=0.875) represented by a mathematical model of optimized microbial cellulose production, Y = -200.437 + 7.180X1 + 69.869X2 + 4.369X3 + 1.867X4 – 0.512X12 – 6.766X22 – 0.585X32 – 0.079X42. From the results, it can be concluded that the foremost factors that affect the production of microbial cellulose in RDR were pH followed by inoculum concentration, disc rotation speed (rpm), and fermentation period.